INDIGENOUS EMPLOYMENT: THE RIO TINTO ALCAN INITIATIVE IN NORTHERN AUSTRALIA - Daff, Sandra; A.L. Pearson, Cecil (The journal of contemporary issues in business and government, 2009)
Recognising that the low labour force participation rate is a primary factor underpinning the significant disadvantages experienced by Indigenous Australians, the Federal Government has targeted job creation through three main avenues: creating the Community Development Employment Projects (CDEP) scheme; expressing commitment to developing business opportunities for economic independence; and strengthening a prevailing assumption that the mining industry will provide Indigenous people in remote areas with employment. This paper reports that: the restructuring of CDEP will lessen employment opportunities for Indigenous people; Indigenous entrepreneurship has not been significant in generating income for Aboriginal people in rural areas; and Australian mining being a substantial employer of Indigenous people in remote areas is yet to be realised. Acknowledging that further research and monitoring is warranted, this paper describes the employment outcomes of Indigenous people who participated in a vocational-educational program conducted by the multinational mining company Rio Tinto Alcan at the remote centre of Nhulunbuy in Australia’s Northern Territory.